On the prevalence of bridged macrocyclic pyrroloindolines formed in regiodivergent alkylations of tryptophan. Issue 7 (16th March 2016) - Rose, Tristin E.; Curtin, Brice H.; Lawson, Kenneth V.; Simon, Adam; Houk, K. N.; Harran, Patrick G.
Abstract : Brønsted acid promotes internal cinnamylations of tryptophan to form structurally complex pyrroloindolines within unique collections of ansa-bridged composite macrocycles. Abstract : A Friedel–Crafts alkylation is described that efficiently transforms tryptophan-containing peptides into macrocycles of varying ring connectivity. Factors are surveyed that influence the distribution of regioisomers, with a focus on indole C3-alkylations leading to bridged endo -pyrroloindolines. We probe the stability and stereochemistry of these pyrroloindolines, study their rearrangement to C2-linked indolic macrocycles, and demonstrate a scalable, stereoselective synthesis of this compound class. Placing the macrocyclization in sequence with further template-initiated annulation leads to extraordinary polycyclic products and further demonstrates the potential for this chemistry to drive novel peptidomimetic lead discovery programs.